Sample instructional materials in communication arts II (English) geared towards the industrial arts curriculum - Ces, Zosita Duran 1949- (1977)
This sample instructional materials in Communication Arts II were prepared in line with the development-oriented education program. These materials are geared towards the national bilingual policy, which places English as the language for international communication, science and technology, and Filipino for social and cultural life. In producing these materials, the writer bore in mind the theory in second language teaching: the acquisition of language skills becomes more meaningful if placed in useful contexts.
"March, 1977."
Vita.
Thesis (M.A.T. English as a Second Language)--University of the Philippines, Diliman.
Keywords: English language -- Study and teaching (Secondary) -- Philippines -- Filipino speakers; Language arts (Secondary) -- Philippines; Second language acquisition; Teaching -- Philippines -- Aids and devices